Correlation of Parental Emotional Support and Career Decision-Making of Student - Sibarani, Senti Okta Maryani; Taufik, Taufik (International Journal of Applied Counseling and Social Sciences, 2025)
This research is motivated by the fact that many students still have difficulty in making career decisions. This condition is identified by the small number of students who are interested in continuing their studies and are confused after graduating from high school, especially in choosing a career. One of the factors that influences career choice decisions is emotional support from both parents. This study aims to describe parental emotional support and students' career decision-making and to describe the relationship between the two variables. This type of research is quantitative research with a descriptive correlational approach. The research sample was 145 students selected using the stratified random sampling technique. The data collection instruments used were the parental emotional support questionnaire and the career decision-making questionnaire. The data were analyzed using percentage, mean, and Pearson product moment correlation statistical techniques. The results of the study showed that: (1) the average score of parental emotional support achievement was 114.45 (72.67%) most students received high parental emotional support, (2) the average score of student career decision-making achievement was 96.76 (62.24%) most students had sufficient career decision-making, (3) there was a significant positive relationship between parental emotional support and student career decision-making with a correlation of 0.468. The findings of the study showed that the results of parental emotional support and career decisions were not optimal, which were still relatively moderate. Guidance and Counseling service interventions were needed to improve both variables.